Elements of international income taxation - Malherbe, Philippe (Bruylant, Groupe Larcier, 2015)
Income taxation is the fuel and vector of the economic policy of many states. This concise book, destined to students, practitioners and policy makers, explains the issues of taxation of transnational income in a world of sovereign states: how to prevent unjust and inefficient double taxation of the same income, by allocating the tax base between source and residence state and properly allowing in the latter for the tax levied in the former? How to prevent abuse by taxpayers or states, furthering tax evasion or avoidance and causing other but equally significant injustices and inefficiencies? Solutions developed over a century of practice are analyzed. That field of the legal art & science is still young and the paradigm for ideal taxation in the global village of the XXIst century is yet to be invented
OCLC: 908334628